PELAKSANAAN TUGAS BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KOTA DUMAI PADA PEMILIHAN UMUM TAHUN 2024 - Utami, Andini Putri; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study is motivated by the persistent weaknesses in the implementation of election supervision during the 2024 General Election in Dumai City, as evidenced by the occurrence of Re-Voting (Pemungutan Suara Ulang/PSU) in nine polling stations. This phenomenon indicates that the preliminary supervision conducted by the General Election Supervisory Agency (Bawaslu) of Dumai City has not been fully effective, particularly in preventing early administrative and technical violations in the field. The purpose of this research is to analyze the implementation of Bawaslu Dumai’s supervisory duties and functions during the 2024 General Election, focusing on the effectiveness of supervision at each stage preliminary, concurrent, and feedback control. This study employs a descriptive qualitative approach with data collected through in-depth interviews and documentation. The analysis is based on Donnelly’s (1996) control theory, which includes three types of supervision: preliminary control, concurrent control, and feedback control, supported by Law Number 7 of 2017 and Bawaslu Regulation Number 5 of 2022 on Election Supervision. The results show that Bawaslu Dumai has generally performed its supervisory duties according to regulations, including prevention, implementation, and enforcement stages. However, preliminary control remains the weakest aspect due to the limited technical training (Bimtek) provided to ad hoc supervisors, weak coordination across supervisory levels, and suboptimal mapping of potential violations. These issues have led to administrative errors that triggered PSU. In conclusion, the implementation of Bawaslu Dumai’s duties during the 2024 General Election has been fairly effective but still requires improvement in preliminary control through capacity building, continuous training, and stronger coordination systems to ensure more credible, fair, and democratic elections in the future. Keywords : Bawaslu Dumai City, Election Supervision, Preliminary Control, Re-Voting (PSU), Donnelly Theory.